PUBLIC RESPON TO CONVERSION PROGRAM OF KEROSENE TO LPG (LIQUID PETROLEUM GAS) AT DESA SIMPANG PETAI KECAMATAN RUMBIOA JAYA KABUPATEN KAMPAR - Rini Septa Dewi; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Public response from Desa Simpang Petai Kecamatan Rumbio Jaya Kabupaten Kampar of kerosene conversion to LPG marked by concrete action of public to conversion program kerosene against LPG or that arise and emerge from the community at the time of the conversion program. The reaction that occurs at the time of the conversion program is a positive response and negative response where positive repon is a response to the acceptance of a new innovation while the negative response is a rejection of the new innovation. Positive response is in the form of a reaction in which Desa Simpang Petai Kecamatan Rumbio Jaya Kabupaten Kampar society receives the conversion program that is being implemented by the government and a negative response from the public Desa Simpang Petai Kecamatan Rumbio Jaya Kabupaten Kampar rejection to the conversion program.Key Words : Response, Conversion, LPG(Liquid Petroleum Gas)